ЗАМОНАВИЙ АХБОРОТ-КОММУНИКАЦИЯ ТЕХНОЛОГИЯЛАРИ АСОСИДА МАСОФАВИЙ ТАЪЛИМ ДАСТУРЛАРИНИ ТАШКИЛ ЭТИШ - Маматов, Д.Н.; Балтабаев, Ж.О. (SCIENCE and SOCIETY, 2020)
The article analyzes the essence, benefits of the introduction of distance learning in higher education institutions, the specifics and problems of modern technologies and foreign experience used in its organization.
Keywords: higher educational establishment distance learning; SMART-technology; webinar; online; «blended learning»; «flipped classroom» technologies; «E-MINBAR» platform; electronic library